Hughes Electrical & Electronic Technology - Hughes, Edward, 1888-; Hiley, John; Brown, Keith, 1962-; Smith, Ian McKenzie (Harlow, England : Pearson, 2016)
All engineers need to understand the fundamental principles of electrical and electronic technology. This best-selling text provides a clear and accessible introduction to the area, with balanced coverage of electrical, electronic, and power engineering.
Previous edition: 2012.
Includes bibliographical references and index.
Keywords: Electrical engineering; Electronics; Technology